Developing Professional Science Teacher Candidates' Teaching Skills Based on Next Generation Science Standards (NGSS) - Parmin, Parmin; Rahayu, Endah Fitriani; Ifriza, Yahya Nur; Siminto, Siminto (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2023)
This study aims to develop the teaching skills of science teacher candidates by integrating Indonesian standards with the criteria of the Next Generation Science Standards (NGSS) through innovative microteaching practices. A mixed-methods approach was used for this research, which targeted science teacher candidates enrolled in microteaching courses, partner teachers, and microteaching lecturers. A total of 20 teacher candidates from a single microteaching class were the subjects of this research. An innovation introduced in this study allowed each student to review and analyze videos of previous microteaching sessions prior to their own practice. Data was collected from the microteaching curriculum, microteaching videos, and effectiveness tests of two developed products. The instrument used was an open-ended observation sheet. Microteaching practices were found to develop the teaching skills of professional science teacher candidates in line with NGSS criteria. Partner teachers reported a variety of positive experiences related to the development of syllabi, lesson plans, teaching materials, student worksheets, and assessments. The positive practices of these partner teachers were used as material for collaboration with lecturers in microteaching courses. The findings of this research indicate that collaboration with teachers in microteaching courses to provide information and feedback to teacher candidates, from preparation and implementation to evaluation of learning, plays a significant role in developing teaching skills.